1991
DOI: 10.1177/027836499101000408
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Motion and Internal Loading of Objects Grasped by Multiple Cooperating Manipulators

Abstract: The motion and internal loads induced on an object manipulated by two or more robotic mechanisms are considered. In particular, for a desired motion trajectory of the object, the question of load distribution among the arms is analyzed, with particular attention given to the internal loading of the object. A new representation of the load distribution problem is given by the introduction of a particular "nonsqueezing" pseudoinverse, which is shown to possess properties that expose the underlying structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(75 citation statements)
references
References 35 publications
(41 reference statements)
0
70
0
Order By: Relevance
“…Hence, two kinds of methods are proposed for the statically indeterminate problem of active overconstrained PMs from the perspective of dealing with the internal forces. The first method is that the driving forces/torques are distributed without internal forces [18,35,70]. A number of studies have shown that the internal forces can be utilized to change the stiffness [79], improve the motion accuracy [32], increase the load-carrying capacity [19], and eliminate the backlash [34] of active overconstrained PMs, so the second method is that the driving forces/torques are distributed by utilizing the advantages of internal forces [19,32,34].…”
Section: Methods Based On the Optimal Internal Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, two kinds of methods are proposed for the statically indeterminate problem of active overconstrained PMs from the perspective of dealing with the internal forces. The first method is that the driving forces/torques are distributed without internal forces [18,35,70]. A number of studies have shown that the internal forces can be utilized to change the stiffness [79], improve the motion accuracy [32], increase the load-carrying capacity [19], and eliminate the backlash [34] of active overconstrained PMs, so the second method is that the driving forces/torques are distributed by utilizing the advantages of internal forces [19,32,34].…”
Section: Methods Based On the Optimal Internal Forcesmentioning
confidence: 99%
“…At present, a variety of optimization goals have been proposed to distribute the driving forces/torques of active overconstrained PMs, such as minimizing the driving forces/torques [29,65], energy consumption [36,66,67], potential energy of the system [37,68,69], internal forces [18,40,70], and improving the traction/load sharing [71]. In essence, the driving forces/torques distribution of active overconstrained PMs under different optimization goals is just a constrained optimization problem, however, the existing methods have not formed a unified one.…”
Section: Introductionmentioning
confidence: 99%
“…The pseudo-inverse K + , called the non-squeezing inverse of K by Walker (1991), is defined by setting it equal to a desired dynamic load distribution matrix L d (Lu and Meng 1992) such that…”
Section: Object Dynamicsmentioning
confidence: 99%
“…Each contact forces solution contains a component that causes the object to move along the reference trajectory and a component that induces internal stress and torsion in the object but does not contribute to its motion. Various approaches for distributing the load have been proposed [7,13,17,18,19,20,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In the explicit control case, some approaches proposed in the literature require knowledge of dynamics of the manipulators and object (e.g., see [lo, 111) while others do not (e.g.. [9]). Most of the approaches that determine the contact forces to optimize a designer specified criteria involve no servoing and assume knowledge of the dynamics of the held object [13,17,18,19,20,291.…”
Section: Introductionmentioning
confidence: 99%